The concept and use of Aisatsu - Saifudin, Akhmad (Japanese Research on Linguistics, Literature, and Culture, 2021)
This paper discusses the use of aisatsu to understand the concept of aisatsu for Japanese people and how Japanese people use aisatsu. The research was conducted using qualitative methods with data sources in recordings and notes from observations and interviews with research subjects. These namely two Japanese students were taking part in summer course activities in Semarang for three days. The approach used in this research is linguistic anthropology with Hymes' ethnographic theory of communication. From the results of data analysis, it was found that aisatsu is used as a greeting, request for permission, an expression of the speaker's feelings, both expressions of apology, gratitude, and feelings of empathy for the speech partner. It was also concluded that the concept of aisatsu is a ritual related to the ethics of politeness and as a sign that represents that the speaker is ready and hopes that his interlocutor is also ready to be involved in the interaction.Tulisan ini mambahas penggunaan aisatsu dalam rangka memahami konsep aisatsu bagi orang Jepang serta bagaimana orang Jepang menggunakan aisatsu. Penelitian dilakukan dengan metode kualitatif dengan sumber data berupa rekaman dan catatan hasil observasi dan wawancara terhadap subjek penelitian, yaitu dua orang mahasiswa Jepang yang sedang mengikuti kegiatan summer course di Semarang selama tiga hari. Ancangan yang digunakan dalam penelitian adalah linguistik antropologi dengan teori etnografi komunikasi Hymes. Dari hasl analisis data ditemukan bahwa aisatsu digunakan sebagai salam, permohonan izin, ungkapan perasaan penutur, baik ungkapan maaf, terima kasih, maupun perasaan empati kepada mitra tutur. Disimpulkan juga bahwa konsep aisatsu merupakan ritual yang berkaitan dengan etika kesopanan dan sebagai tanda yang merepresentasikan bahwa penutur telah siap serta berharap mitra tuturnya juga siap untuk terlibat dalam interaksi.